Partisipasi Masyarakat Dalam Penanggulangan Abrasi Pantai - Samarudin; Surdin; La Harudu (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Batu Gong Village is one of the coastal areas in Southeast Sulawesi Province. This area has a coastline of 300 m and has long experienced coastal abrasion due to sea waves and ocean currents. The purpose of this study was to describe community participation in overcoming beach abrasion in Batu Gong Village, Lalonggasumeeto District, Konawe Regency. This type of research is mixed research (mixed methods) with convergent parallel designs and the number of respondents is 31 people. Data in this study were collected through observation, questionnaires, interviews and documentation. The results of the study show that the level of community participation in terms of thinking is more dominant than the participation in implementation and property participation. Furthermore, community participation in overcoming coastal abrasion in Batu Gong Village, Lalonggasumeeto District, Konawe Regency is generally in the unfavorable category.